Is the field of organic thermoelectrics stuck? - Brunetti, Irene; Dash, Aditya; Scheunemann, Dorothea; Kemerink, Martijn (Journal of materials research, 2024)
With the rising popularity of organic thermoelectrics, the interest in doping strategies for organic semiconductors has increased strongly over the last decade. Here, we use aggregate data to discuss how far the approaches pursued till date have brought the community in terms of typical performance indicators for doped semiconductors in the context of thermoelectric applications. Surprisingly, despite the superlinear increase in the number of publications on the subject matter, the performance indicators show no clear upward trend in the same time range. In the second part, we discuss possible approaches to break this deadlock. A specifically promising approach, controlling the distribution of dopant atoms in the host material, is discussed in some quantitative detail by experiments and numerical simulations. We show that spontaneous modulation doping, that is, the spatial separation between static dopant ions and mobile charge carriers, leads to a dramatic conductivity increase at low dopant loading.
Gesehen am 14.08.2024